(untitled) (World Economics and Finance Bulletin, 2025)
This article examines the evolution of managing mass media and communication tools (MMCT) in education from the early 20th century to the contemporary digital era, with a particular focus on the managerial transformation from centralized, directive control to flexible, network-oriented, and outcome-driven systems. Using Uzbekistan as a primary case study, supplemented by comparative examples from Finland and Singapore, the research explores how educational management practices have adapted to the rapid integration of digital technologies, the rise of personalized learning environments, and the increasing importance of strategic communications in education. The article outlines methodological approaches to analyzing MMCT implementation, evaluates the impact of technological change on management strategies, and proposes recommendations for building sustainable and inclusive educational media ecosystems.